Effect of Air Purification Systems on Particulate Matter and Airborne Bacteria in Public Buses - Lee, Jae Jung; Hwang, Hyemin; Hong, Suk Chan; Lee, Jae Young (Atmosphere, 2022)
The indoor air quality in public transport systems is a major concern in South Korea. Within this context, we investigated the effect of air purification systems on the indoor air quality of intercity buses, one of the most popular transport options in South Korea. Air purifiers were custom designed and equipped with high-efficiency particulate air (HEPA) filters to remove particulate matter and ultraviolet light-emitting diodes (UV-LEDs) to remove airborne bacteria. To investigate the effectiveness of the air purification systems, we compared concentrations of particulate matter (PM2.5 and PM10 ), airborne bacteria, and carbon dioxide (CO2 ) in six buses (three with air purification systems and three without) along three bus routes (BUS1, BUS2, BUS3) in Gyeonggi Province, South Korea, between 6 April and 4 May 2021. Compared to the buses without air purification, those with air purification systems showed 34–60% and 25–61% lower average concentrations of PM2.5 and PM10, respectively. In addition, buses with air purification systems had 24–78% lower average airborne bacteria concentrations compared to those without air purification systems (when measured after 30 min of initial purification).
Keywords: Air purification systems; Air purifier; Airborne bacteria; Indoor air quality; Intercity bus; Lower average; Particulate Matter; PM 10; PM 2.5; South Korea; Air purifier; Airborne bacteria; CO2; Indoor air quality; Intercity bus; PM10; PM2.5